KIPLING’S BRITISH WORLDVIEW ON COLONIZATION IN KIPLING’S KIM - Kusuma, Anggar (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2012)
This paper analyzes how Kipling who was known as the supporter of the British Empire expressed his British worldview towards British colonization over India through his novel Kim. It aims to reveal Kipling’s British worldview and its impact towards ex-colonial countries in post-colonial context. This paper is a descriptive, qualitative research. The data were taken from novel Kim and in the form of text. The paper also employed Post-colonialism and genetic structuralism theories. The analysis of the paper results in several findings. The theme of novel Kim is about an identity crisis between white or native faced by a white person as an impact of colonization. The setting of novel Kim takes places in India during British colonial rule. There are many Kipling’s life that are reflected in novel Kim namely Kipling’s school phase, Kipling’s career, Kipling’s relationship with Freemansory, and some people who become the models of some characters in the novel. Through novel Kim, Kipling seems expressing his British worldview on colonization, persuading that British colonization in essence gave benefits to India. Lastly, the implication of the worldview has influenced the people of India, the representative of ex-colonial countries, both in thinking and behavior.